Pengelolaan Agroforestri Kopi Berbasis Wisata di Dawuhan Kopi, Kabupaten Semarang - Suwarti Suwarti; Aurilia Triani Aryaningtyas (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2025)
Tourism is currently a rapidly growing sector, particularly in line with social change and technological advancements. In this context, ecotourism is becoming an increasingly popular approach because it prioritizes the principles of environmental sustainability, local cultural preservation, and improving community welfare. One innovative form of ecotourism is the development of agroforestry-based tourism, which integrates environmentally friendly agricultural and forestry practices. One concrete example of this concept is the Dawuhan Kopi area in Semarang Regency. This area has developed a coffee forest farming system as a primary tourist attraction, aiming to combine nature conservation and community economic development. This study aims to comprehensively examine how coffee agroforestry management in Dawuhan Kopi is implemented as a form of ecotourism and to analyze various optimization efforts that have been and are being implemented. The research method used is a qualitative descriptive approach with data collection techniques such as field observations, in-depth interviews with stakeholders, and documentation. The results reveal that the management of the coffee agroforestry area in Dawuhan Kopi still faces various challenges, particularly in terms of institutional framework, tourism product packaging, availability of supporting facilities, and local community empowerment. To address these issues, a comprehensive improvement strategy is needed, ranging from strengthening institutional capacity, innovation in tourism packages, developing basic infrastructure, and increasing active community participation in every management process. This research is expected to make a positive contribution to the development of a sustainable agroforestry-based ecotourism model and serve as a reference for other regions with similar potential to implement the same concept adaptively and contextually.